Protective Cytomegalovirus (CMV)-Specific T-Cell Immunity Is Frequent in Kidney Transplant Patients without Serum Anti-CMV Antibodies - Litjens, Nicolle H. R.; Huang, Ling; Dedeoglu, Burç; Meijers, Ruud W. J.; Kwekkeboom, Jaap; Betjes, Michiel G. H. (Frontiers in Immunology, 2017)
The absence of anti-CMV IgG is used to classify pre-transplant patients as naïve for CMV infection (CMVneg patients). This study assessed whether pre-transplant CMV-specific T-cell immunity exists in CMVneg patients and whether it protects against CMV-infection after kidney transplantation. The results show that CMV-specific CD137+IFNγ+CD4+ and CD137+IFNγ+CD8+ memory T cells were present in 46% and 39% of CMVneg patients (n=28) although at much lower frequencies compared to CMVpos patients (median 0.01% versus 0.58% for CD4+ and 0.05% versus 0.64% for CD8+ T cells) with a less differentiated CD28-expressing phenotype. In line with these data, CMV-specific proliferative CD4+ and CD8+ T cells were observed in CMVneg patients, which significantly correlated with the frequency of CMV-specific T cells. CMV-specific IgG-antibody secreting cells (ASC) could be detected at low frequency in 36% of CMVneg patients (1 versus 45 ASC/105 cells in CMVpos patients). CMVneg patients with pretransplant CMV-specific CD137+IFNγ+CD4+ T cells had a lower risk to develop CMV-viremia after transplantation with a CMVpos donor kidney (relative risk: 0.43, p=0.03). In conclusion, a solitary CMV-specific T-cell response without detectable anti-CMV antibodies is frequent and clinically relevant as it is associated with protection to CMV-infection following transplantation with a kidney from a CMVpos donor.